Locating of New Cities and Soil variability (Journal of the College of Basic Education, 2022)
The fertility of the land in the whole province of Babylon and its small size, and considering that its center is the city of Hilla of large cities that suffer from multiple problems on various sectors, especially the creation of residential land, made the policy of new cities one of the solutions used in dealing with these many and varied problems with the presence of the initiative by the state to establish new cities in all provinces, the problem of research was the existence of the challenge of determining the appropriate location of the new city in Babil province according to traditional methods and not taking into account the soil source for the future problems of these cities. The aim is to make the appropriate planning decision for the spatial signature of the new cities in accordance with the appropriate planning methods and local standards to ensure their efficiency and ease of implementation and to ensure future axes for long-term expansion and attention to the soil standard when selecting the site. The hypothesis of the research is to balance the importance of soil with geographical and environmental planning standards and important elements to be taken into account when locating a new city as part of a sound urban system using modern technologies and software. The concept of a new city, which is part of the policy of urban spread and theories of urban and regional planning organized for this policy, and the types of soil supporting the urban structures and urban environment suitable for those cities, should also be identified. One of the most important conclusions of the research is not to view the new cities as urban expansion of large cities and to move away from the mother city appropriate planning distance. The selection of the appropriate soil for these cities in a balanced manner with other criteria as a fundamental supporter of all different uses of land, one of the most important recommendations was to consider the new city as a comprehensive rural and urban development, and to take care of the soil as an important criterion because it will require treatment for each square meter of the selected area, i.e. for each housing unit, each road and various other uses, causing an increase in the cost of establishing those cities.